Profiling indigenous lead-reducing bacteria from Tempe Lake, South Sulawesi, Indonesia as bioremediation agents - AHMAD YANI; MOHAMAD AMIN; Fatchur Rohman; ENDANG SUARSINI; WIRA EKA PUTRA (Society for Indonesian Biodiversity, 2020)
Abstract. Yani A, Amin M, Rohman F, Suarsini E, Putra WE. 2020. Profiling indigenous lead-reducing bacteria from Tempe Lake, South Sulawesi, Indonesia as bioremediation agents. Biodiversitas 21: 4778-4786. The pollution of heavy metals by anthropogenic activities in freshwater, especially in lakes, reduces the quality and endangers the existence of aquatic flora and fauna. This happens in Lake Tempe, which is located, in South Sulawesi, Indonesia. The study aimed to evaluate the content of heavy metals, isolation, and identify a lead reduction of indigenous bacteria as candidates for bioremediation agents. It began by examining the level of cadmium (Cd), copper (Cu), and lead (Pb) in seven sampling sites of Tempe Lake. Furthermore, propagation and isolation, morphological observation, laboratory-scale reduction tests, and species identification of potential bacteria reduction Pb were performed by using 16s rDNA. The reduction test to Pb was measured using Atomic Absorption Spectrometry (AAS), and the research data were analyzed using One-Way ANOVA with the Duncan advanced method. The results showed that the Cd, Cu, and Pb content of the seven sampling points exceeded the water quality standard Following the Indonesian Government Regulation (IGR) and WHO standards. Pb has the highest concentration among the other heavy metals in the water sample reaching 0.40 mg/L. Four bacterial isolates could grow on Pb-enriched media (isolates A, B, C, and D). The Bacillus form was found in two different species bacteria (isolate A and D), while the cocci shape was found in two other species (isolate B and C). Those all Gram-negative bacteria were observed to be a reduction to Pb exposure within a bacterial medium. Interestingly, these indigenous bacteria could decrease Pb concentration ranging from 7.45 to 3.48 ppm for seven days. Furthermore, the sequencing data showed that the indigenous bacteria (isolate D) had a 99.90% similarity to the Comamonas testosteroni strain S-2 constructed using Neighbor-joining phylogenetic analysis. Therefore, the indigenous bacteria C. testosteroni strain S-2 from Tempe lake may be proposed as a bioremediation agent to reduce Pb the water contaminants.